Design challenges and preliminary test results of a high temperature supercritical carbon dioxide dry gas seal test rig - Abdeldayem, Abdelrahman; Kissoon, Sajal; Anselmi Palma, Eduardo (University of Duisburg, Essen, 2025)
Supercritical carbon dioxide (sCO2) has shown a high potential in power generation cycles to increase thermal efficiency and decrease the physical footprint. Supercritical CO2 power cycles operate at relatively high temperatures compared to steam and air, necessitating the development of new sealing materials. In this paper, the design challenges, development and preliminary test results of a 500oC, 200 bar sCO2 dry gas seals test rig are presented. The main rig components are pressure control devices (liquid pump and expansion valves), heat exchangers (liquid condenser, gas heaters, and air cooler), and measuring instruments. Various design challenges are identified due to the thermo-physical properties as well as the operating conditions of the sCO2 test rig such as the ice formation during start-up, heat loss to the ambient air, and material compatibility with the various test rig components. A thermodynamic design model has been developed to size the test rig components and estimate the gas conditions across the rig. The model includes tube and valve sizing, heat exchanger design, and thermal insulation models. The initial phase of the test campaign was conducted at Cranfield University (CU) to verify the ability of the test rig to deliver sCO2 at the required conditions and to validate the developed numerical models. The results showed the validity of the proposed setup to supply sCO2 steadily at 500oC and 200 bar at a flow rate of 15 kg/h. The heat exchanger model applied to a finned tube bundle air cooler showed close estimations to the test results with a maximum deviation in the heat capacity of 2.3%. The thermal insulation model including the heating tape showed reasonable predictions for the temperature rise across the heating sections with a maximum deviation from the experimental measurements of 10oC when the temperature rise was around 240oC. The suitability of using rock wool insulation and stainless steel 316 tubes with dry CO2 at 500oC was verified.
Keywords: supercritical CO2; experimental; high temperature; dry gas seal; modelling